(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
تعتبر طرز القرع العسلي مصدرا هاما من مصادر التباين يمكن استخدامه كمادة أساسية في برامج التربية لتحسين صفات هذا المحصول. وقد خضعت الطرز المحلية من قرع الموسكاتا العسلي Duch , Cucurbita moschata والبالغ عددها / 9 / طرز لدراسة استمرت من عام 2001 إلى 2003 شملت الأطوار الفينولوجية للنبات وبعض الصفات الاقتصادية وأهم الصفات الكمية لاسيما المكونة للإنتاجية وذلك بهدف تقييم صفات كل طراز وتحديد الطرز الاقتصادية والاستفادة منها في عمليات التربية وتحسين صفات الطرز المزروعة. أظهرت دراسة النتائج وجود تباينات وراثية ضمن المجموعات و بينها وذلك لعدد من الصفات الاقتصادية الهامة ( طول الساق – عدد العقد غير الثمرية على الساق الرئيسية– النسبة الجنسية– متوسط وزن الثمرة الواحدة – عدد الثمار على النبات – متوسط وزن 100بذرة ).. كما أظهرت النتائج وجود علاقة ارتباطية إيجابية بين صفة الإنتاجية و عدد من الصفات الاقتصادية الهامة مثل ( طول الساق – عدد السلاميات – النسبة الجنسية – عدد الثمار على النبات – متوسط وزن الثمرة ) وأنه يمكن اعتماد صفة متوسط وزن الثمرة كدليل انتخاب لصفة الإنتاجية يليه صفة طول الساق ومن ثم متوسط عدد الثمار على النبات. The local types of Pumpkin is considered as a rich source of variation and can be used as a main selection material in breeding programs to improve the characteristics of this crop. In this research, nine local types of Pumpkin (Cucurbita moschata ,Duch) have been studied from 2001 to 2003. The study included plant phonological phases, economical characteristics, and the most important quantitative characteristics relating to fruit yield to evaluate the characteristics of every type and identify the economical types to use in the breeding programs. The study of results showed genetic variation between the groups for some important economic characteristic as (stem long. No of nodes till the first female flower, sexual ratio ♀/♂, fruit average weight, the average weight of 100 seeds). The results appeared also the positive correlation between the productivity and some important economic characteristics, such as (stem long, nodes number, sexual ratio ♀/♂, the average weight of fruit, the number of fruits per plant). this means that we can consider the weight fruit character, as selection index for productivity character followed by the steam long characteristics, number of fruits per plant.